Improving the resilience of disaster management organizations through virtual communities of practice: A Delphi study. (9th August 2017) - Gimenez, Raquel; Hernantes, Josune; Labaka, Leire; Hiltz, Starr Roxanne; Turoff, Murray
Abstract : A resilience‐focused approach leads organizations to improve the management of disasters through being aware, flexible, trained, and prepared, having committed top managers and staff, and being part of a wider network of stakeholders. Based on the organizational resilience principles identified in the literature, this article analyses the potential for improvement of the organizational resilience of disaster management organizations through their involvement in virtual communities of practice (VCoPs). VCoPs are groups of stakeholders from different organizations with a common interest that collaborate and exchange knowledge on a regular basis. This article presents a Delphi study that was conducted with a multidisciplinary group of international experts that work in disaster management organizations to evaluate the contribution of VCoPs. The results of the Delphi show that VCoPs help organizations to improve the organizational resilience principles. Nevertheless, there is still a series of barriers that organizations need to face in terms of collaboration and information sharing. This article classifies the existing barriers that hinder participation in VCoPs and suggests solutions to overcome them.